The Silence Bissu: Cultural Misaccommodation of Local Communities in Ritual Ceremony - Pabbajah, Mustaqim; Adawiah, Rabiatul; Darwis, Muh (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
This article aims to explain how cultural misaccommodation of rituals in local communities can occur. Bissu as a component of society comes along with negotiations to maintain the rituals and religiosity that have shaped their identity. The presence of bissu in the ritual procession is an authority that they have culturally. Throughout the history of civilisation, bissu were the main, sacred and central party in the ritual procession. However, what happened on Bone's 62nd anniversary was a moment when bissu were not involved. This article is based on data obtained from online searches. News and article searches were conducted as a basis for analysing the cultural misaccommodation of local communities. This article shows that the misaccommodation of bissu in the ritual procession is a weakening of identity and existence. The government in this case becomes the party that eliminates bissu from its roots, the dynamics of polarisation of the ruling group along with a set of laws make bissu misaccommodation a hegemony. Along with the society that places bissu as a minority party, both socially and culturally. Therefore, it is necessary to affirm the authority of bissu as a party that maintains cultural sustainability.